Alwilkinsite-(Y), a new rare-earth uranyl sulfate mineral from the Blue Lizard mine, San Juan County, Utah, USA. (1st August 2017) - Kampf, Anthony; Plášil, Jakub; Čejka, Jiří; Marty, Joe; Škoda, Radek; Lapčák, Ladislav
The new mineral alwilkinsite-(Y) (IMA2015-097), Y(H2O)7[(UO2)3(SO4)2O(OH)3]·7H2O, was found in the Blue Lizard mine, San Juan County, Utah, USA, where it occurs as a secondary alteration phase. The mineral is slightly flexible before brittle failure with splintery fracture and perfect cleavage parallel to [010], has Mohs hardness of ∼2–2½, exhibits dull greenish-grey fluorescence and has a calculated density of 3.371 g cm–3. Alwilkinsite-(Y) occurs as yellowish-green needles, elongate on [010], with domatic terminations and exhibits the forms {102}, {301} and {124}. It is optically biaxial (+) with α = 1.573(1), β = 1.581(1), γ = 1.601(1) (white light), the measured 2V is 65.3(1)°, the dispersion is r < v (weak), the optical orientation is X = c, Y = a, Z = b and there is no pleochroism. Electron microprobe analyses yielded the empirical formula (Y0.66Dy0.08Gd0.06Er0.05Nd0.03Yb0.03Sm0.02Ce0.01)∑0.94(H2O)7[(UO2)3(S1.01O4)2O(OH)3]·7H2O. The eight strongest powder X-ray diffraction lines are [dobs Å(I)(hkl)]: 9.88(100)(101, 002), 7.47(13)(102), 5.621(17)(103, 201), 4.483(18)(104), 3.886(14)(130, 222), 3.322(46)(multiple), 3.223(13)(multiple) and 3.145(16)(034). Alwilkinsite-(Y) is orthorhombic, P212121, a = 11.6194(5), b = 12.4250(6), c = 19.4495(14) Å, V = 2807.9(3) Å3 and Z = 4. The structure of alwilkinsite-(Y) (R1 = 0.042 for 4244 Fo > 4σF) contains edge-sharing chains of uranyl bipyramids with outlying sulfate tetrahedra that are similar to the chain linkages within the uranyl sulfate sheets of the zippeite structure. Short segments of the uranyl sulfate chains in the alwilkinsite-(Y) structure have the same topology as portions of the uranyl sulfate linkages in uranopilite. Alwilkinsite-(Y) is named for Alan (Al) J. Wilkins, MD (born 1955), the discoverer of the mineral.